2008
DOI: 10.1534/genetics.107.084202
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Chd1 and Set2 in Negatively Regulating DNA Replication in Saccharomyces cerevisiae

Abstract: Chromatin-modifying factors regulate both transcription and DNA replication. The yFACT chromatinreorganizing complex is involved in both processes, and the sensitivity of some yFACT mutants to the replication inhibitor hydroxyurea (HU) is one indication of a replication role. This HU sensitivity can be suppressed by disruptions of the SET2 or CHD1 genes, encoding a histone H3(K36) methyltransferase and a chromatin remodeling factor, respectively. The additive effect of set2 and chd1 mutations in suppressing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 77 publications
4
38
0
Order By: Relevance
“…The FACT complex plays an important role in DNA replication (6,54,57,58), and our results suggest that the NuA4 KAT complex is also involved in DNA replication. A mutation in the Esa1 catalytic subunit results in mild sensitivity to HU, and an spt16 esa1 double mutant shows additivity in HU sensitivity.…”
Section: Discussionsupporting
confidence: 56%
“…The FACT complex plays an important role in DNA replication (6,54,57,58), and our results suggest that the NuA4 KAT complex is also involved in DNA replication. A mutation in the Esa1 catalytic subunit results in mild sensitivity to HU, and an spt16 esa1 double mutant shows additivity in HU sensitivity.…”
Section: Discussionsupporting
confidence: 56%
“…5C and 5D), indicative of a transcription elongation defect. We and others have shown that set2D bypasses the slow growth phenotype of spt16-11 at semi-permissive temperature (of 35 C) 68,69 and that set2D is resistant to 6-AU. 36 Since FACT is a positive regulator of transcription elongation, and 6-AU results in elongation defects, bypass of spt16-11 mutant and resistance to 6-AU suggests Set2 as a negative regulator of transcription elongation.…”
Section: Association Ofmentioning
confidence: 74%
“…At least some FACT mutants retain normal induction of RNR gene transcription (Biswas et al 2008;Formosa 2008), so HU sensitivity often reflects a defect in DNA replication, but indirect effects due to flawed transcription are also possible. The Spt 2 phenotype results from inappropriate transcription initiation start-site selection (Clark-Adams et al 1988), indicating that spt16-11 causes a defect in transcription even at temperatures permissive for growth where Spt16 protein levels are normal.…”
Section: Resultsmentioning
confidence: 99%
“…Some features of chromatin therefore support FACT activity in vivo, and their loss makes FACT defects more difficult to tolerate. In contrast, other chromatin factors oppose FACT activity, as the phenotypes caused by some FACT gene mutations can be suppressed by preventing methylation of H3-K36 (Biswas et al 2006) or by inactivating the chromodomain-helicase Chd1 (Biswas et al 2008). FACT gene mutations can also either enhance or suppress defects caused by mutating other chromatin factors such as the histone H3 or the Swi/Snf remodeling complex (Malone et al 1991;Duina et al 2007).…”
mentioning
confidence: 99%